2013
DOI: 10.1371/journal.pone.0081526
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Mechanism for Recognizing Substrate of the Cytochrome P450 Enzyme TxtE

Abstract: Thaxtomins, a family of phytotoxins produced by Streptomyces spp., can cause dramatic plant cell hypertrophy and seedling stunting. Thaxtomin A is the dominant form from Streptomyces scabies and has demonstrated herbicidal action. TxtE, a cytochrome P450 enzyme from Streptomyces scabies 87.22, catalyzes direct nitration of the indolyl moiety of L-tryptophan to L-4-nitrotryptophan using nitric oxide, dioxygen and NADPH. The crystal structure of TxtE was determined at 2.1 Å resolution and described in this work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 34 publications
4
33
1
Order By: Relevance
“…used AutoDock to propose three L-tryptophan binding poses. [13] The binding orientation observed in our study closely resembles their first two proposals. As shown in Figure 2b, the tryptophan (which is bound to approximately 80% occupancy) binds with its indole side chain facing into the distal face of the heme, displacing the water that ligates the heme (this water is still visible in the tryptophan-bound structure, refined at 20% occupancy).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…used AutoDock to propose three L-tryptophan binding poses. [13] The binding orientation observed in our study closely resembles their first two proposals. As shown in Figure 2b, the tryptophan (which is bound to approximately 80% occupancy) binds with its indole side chain facing into the distal face of the heme, displacing the water that ligates the heme (this water is still visible in the tryptophan-bound structure, refined at 20% occupancy).…”
Section: Resultssupporting
confidence: 89%
“…Residues Met88 and Phe395 define the hydrophobic cleft for the substrate’s indole moiety. The C-4 position of the indole ring, the site of nitration, faces away from the heme and toward the hydroxyl of Tyr89 and the solvent channel that was identified previously [13] and confirmed in our structures. In the substrate-free structure, three ordered waters define this solvent channel as reported, [13] whereas in the tryptophan-bound structure a tube of indistinct density is visible that could not be modeled as waters.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The second P450, TxtE, 274,301 performs an even more intriguing transformation: the regiospecic 4-nitration of the indolyl moiety of L-tryptophan. 274 Subsequent studies have also shown that TxtE has tolerance for certain alternate substrates.…”
mentioning
confidence: 99%